Carotid Ultrasound Boundary Study (CUBS): An Open Multicenter Analysis of Computerized Intima-Media Thickness Measurement Systems and Their Clinical Impact - Meiburger, Kristen M.; Zahnd, Guillaume; Faita, Francesco; Loizou, Christos P.; Carvalho, Catarina; Steinman, David A.; Gibello, Lorenzo; Bruno, Rosa Maria; Marzola, Francesco; Clarenbach, Ricarda; Francesconi, Martina; Nicolaides, Andrew N.; et al. (My University, 2021)
Common carotid intima-media thickness (CIMT) is a commonly used marker for atherosclerosis and is often computed in carotid ultrasound images. An analysis of different computerized techniques for CIMT measurement and their clinical impacts on the same patient data set is lacking. Here we compared and assessed five computerized CIMT algorithms against three expert analysts' manual measurements on a data set of 1088 patients from two centers. Inter- and intra-observer variability was assessed, and the computerized CIMT values were compared with those manually obtained. The CIMT measurements were used to assess the correlation with clinical parameters, cardiovascular event prediction through a generalized linear model and the Kaplan-Meier hazard ratio. CIMT measurements obtained with a skilled analyst's segmentation and the computerized segmentation were comparable in statistical analyses, suggesting they can be used interchangeably for CIMT quantification and clinical outcome investigation. To facilitate future studies, the entire data set used is made publicly available for the community at http://dx.doi.org/10.17632/fpv535fss7.1.
Keywords: Atherosclerosis; Cardiovascular events; Carotid artery intima–media thickness; Open-source database; Segmentation; Ultrasound imaging